2017
DOI: 10.1002/adma.201701466
|View full text |Cite
|
Sign up to set email alerts
|

Electric‐Field‐Controlled Dopant Distribution in Organic Semiconductors

Abstract: Stable electrical doping of organic semiconductors is fundamental for the functionality of high performance devices. It is known that dopants can be subjected to strong diffusion in certain organic semiconductors. This work studies the impact of operating conditions on thin films of the polymer poly(3-hexylthiophene) (P3HT) and the small molecule Spiro-MeOTAD, doped with two differently sized p-type dopants. The negatively charged dopants can drift upon application of an electric field in thin films of doped P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 34 publications
3
49
0
Order By: Relevance
“…[ 38 ] We also note that in previous measurements of P3HT/F4TCNQ samples, when a high potential is applied, the F4TCNQ − ions drift in the electric field and therefore move during a conductivity measurement. [ 39 ] The electric field applied here is far lower. We have no evidence that the distribution of F4TCNQ − ions changed during our measurements.…”
Section: Resultsmentioning
confidence: 99%
“…[ 38 ] We also note that in previous measurements of P3HT/F4TCNQ samples, when a high potential is applied, the F4TCNQ − ions drift in the electric field and therefore move during a conductivity measurement. [ 39 ] The electric field applied here is far lower. We have no evidence that the distribution of F4TCNQ − ions changed during our measurements.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, g m exhibited a near‐ideal ascent stage that g m dramatically increased with V G from 5 V and then saturated at V G of ≈−10 V. It has been reported that some molecular dopants such as F4‐TCNQ tended to migrate in organic films under the electric field force. The migration of dopant molecules into the active channel under the electric field force may also give rise to the performance improvement . To eliminate this possibility, the con‐doped devices with channel length of 200 µm was characterized for comparison, since the drift of molecular dopants is known to take place only within a length scale of micrometers under the electric field force .…”
Section: Resultsmentioning
confidence: 99%
“…a School of Biological and Chemical Sciences, Queen Mary University of London, solid state, in particular at elevated temperatures, and drift due to applied electric fields, potentially reducing device lifetimes. 16,17 Recently, molecular engineering of semiconductors and dopants has been employed as a tool to control dopant diffusion and polymer:dopant interactions. One well-explored strategy is to introduce ethylene glycol motifs into the polymer side chain.…”
Section: Introductionmentioning
confidence: 99%